A MicroRNA-Transcription Factor Blueprint for Early Atrial Arrhythmogenic Remodeling. (28th June 2015) - Torrado, Mario; Franco, Diego; Lozano-Velasco, Estefanía; Hernández-Torres, Francisco; Calviño, Ramón; Aldama, Guillermo; Centeno, Alberto; Castro-Beiras, Alfonso; Mikhailov, Alexander
Abstract : Spontaneous self-terminating atrial fibrillation (AF) is one of the most common heart rhythm disorders, yet the regulatory molecular mechanisms underlying this syndrome are rather unclear. MicroRNA (miRNA) transcriptome and expression of candidate transcription factors (TFs) with potential roles in arrhythmogenesis, such as Pitx2, Tbx5, and myocardin ( Myocd ), were analyzed by microarray, qRT-PCR, and Western blotting in left atrial (LA) samples from pigs with transitory AF established by right atrial tachypacing. Induced ectopic tachyarrhythmia caused rapid and substantial miRNA remodeling associated with a marked downregulation of Pitx2, Tbx5, and Myocd expression in atrial myocardium. The downregulation of Pitx2, Tbx5, and Myocd was inversely correlated with upregulation of the corresponding targeting miRNAs (miR-21, miR-10a/10b, and miR-1, resp.) in the LA of paced animals. Through in vitro transient transfections of HL-1 atrial myocytes, we further showed that upregulation of miR-21 did result in downregulation of Pitx2 in cardiomyocyte background. The results suggest that immediate-early miRNA remodeling coupled with deregulation of TF expression underlies the onset of AF.